TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN TUBERKULOSIS - Umi Nafisah; Riyan Setiyanto; Rahmadhani Tyas Angganawati; Runtut Wigati; Erna Wati (Jurnal Farmasindo, 2021)
The number of new tuberculosis cases in Indonesia is still ranked third in the world and is one of the biggest challenges facing Indonesia and requires attention from all parties, because it provides a high burden of morbidity and mortality. Tuberculosis (TB) is the highest cause of death after ischemic heart disease and cerebrovascular disease. The purpose of this study was to find out how big the level of adherence of tuberculosis patient in treatment and taking medication. The type of research used is research that is descriptive. The sample was used by 47 respondents. Data retrieval uses purposive sampling. The data was taken using validated questionnaires based on MMAS-8 (Morisky Medication Adherence Scale). The results of this study showed that 72% had high compliance rates, 15% for moderate compliance levels, and as many as 13% were in low compliance levels. The conclusion of the level of adherence to taking drugs in tuberculosis patients in Sibela Health Center with the above value is that 72% has a high compliance rate of 64 respondents.